FTY720 attenuates excitotoxicity and neuroinflammation - Cipriani, Raffaela (J Neuroinflammation, 2015)
BACKGROUND: FTY720 (fingolimod, Gilenya™), a structural analog of sphingosine-1-phosphate (S1P), is the first oral drug approved for treatment the relapsing-remitting form of multiple sclerosis (MS), and its efficacy has been related to induced lymphopenia and consequent immunosuppression via modulation of S1P(1) receptors (S1P(1)R). However, due to its lipophilic nature, FTY720 crosses the blood brain barrier (BBB) and could act directly on neural cells. In this study, we investigated the effectiveness of FTY720 as a neuroprotective agent using in vitro and in vivo models of excitotoxic neuronal death and examined if FTY720 exerts a direct action on neurons, or/and an indirect modulation of inflammation-mediated neurodegeneration as a possible mechanism of neuroprotection. METHODS: Primary neuronal and organotypic cortical cultures were treated with N-methyl-D-aspartic acid (NMDA) to induce excitotoxic cell death (measured by lactate dehydrogenase (LDH) assay or propidium iodide uptake, respectively). The effects of FTY720 treatment (10, 100 and 1,000 nM) on neuronal survival were examined. As an in vivo model of neuronal death and inflammation, we used intracerebroventricular (icv) administration of kainic acid (KA; 0.5 μg/2 μl) in Sprague–Dawley rats. FTY720 was applied icv (1 μg/2 μl), together with KA, plus intraperitoneally (ip; 1 mg/kg) 24 h before, and daily, until sacrifice 3 days after icv. Rats were evaluated for neurological score, neuronal loss in CA3 hippocampal region and activation of microglia at the lesion site. In addition, we tested FTY720 as a modulator of microglia responses using microglial cell cultures activated with lipopolysaccharide (LPS) and its effects in stress signalling pathways using western blotting for p38 and JNK1/2 mitogen-activated protein kinases (MAPKs). RESULTS: FTY720 was able to reduce excitotoxic neuronal death in vitro. Moreover, in vivo repeated FTY720 administration attenuated KA-induced neurodegeneration and microgliosis at the CA3 lesion site. Furthermore, FTY720 negatively modulates p38 MAPK in LPS-activated microglia, whereas it had no effect on JNK1/2 activation. CONCLUSIONS: These data support a role for FTY720 as a neuroprotective agent against excitotoxin-induced neuronal death and as a negative modulator of neuroinflammation by targeting the p38 MAPK stress signalling pathway in microglia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-015-0308-6) contains supplementary material, which is available to authorized users.